PESAN TERSIRAT DALAM LAGU “BALUR”: KAJIAN PRAGMATIK DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA DI SMA - Salwa Hafizhah; Afifah Oktaviani (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to reveal the implicit messages contained in the song Balur by Cik Din Syahri S.M. through a pragmatic approach and to describe its implications for Indonesian language learning at the senior high school level. The research employed a qualitative method with a content analysis approach based on Austin and Searle’s theory of speech acts. The primary data consisted of the lyrics of Balur, analyzed through data reduction, categorization, and thematic interpretation, while supporting data were obtained from interviews with teachers and students to evaluate the song’s relevance as learning material. The findings show that Balur contains illocutionary, expressive, and perlocutionary speech acts reflecting social criticism toward inequality and human suffering. Moral messages are conveyed indirectly through metaphors and repetition that evoke emotional awareness among listeners. The song is proven relevant as a language learning medium because it integrates cultural, social, and character values that are contextually related to students’ lives. The novelty of this study lies in applying pragmatic theory to a regional Lampung song and linking it directly to high school learning contexts, expanding the scope of pragmatic studies from linguistic to educational and cultural domains while enriching pragmatic literacy based on local wisdom.